MOF‐Based Transparent Passivation Layer Modified ZnO Nanorod Arrays for Enhanced Photo‐Electrochemical Water Splitting. Issue 18 (24th March 2018) - Li, Xiao; Liu, Shengwei; Fan, Ke; Liu, Zhaoqing; Song, Bo; Yu, Jiaguo
Abstract: This study introduces zeolitic imidazolate framework‐8 (ZIF‐8) as the first metal‐organic framework based transparent surface passivation layer for photo‐electrochemical (PEC) water splitting. A significant enhancement for PEC water oxidation is demonstrated based on the in situ seamless coating of ZIF‐8 surface passivation layer on Ni foam (NF) supported ZnO nanorod arrays photoanode. The PEC performance is improved by optimizing the ZIF‐8 thickness and by grafting Ni(OH)2 nanosheets as synergetic co‐catalyst. With respect to ZnO/NF, the optimized Ni(OH)2 /ZIF‐8/ZnO/NF photoanode exhibits a two times larger photocurrent density of 1.95 mA cm −2 and also a two times larger incident photon to current conversion efficiency of 40.05% (350 nm) at 1.23 V versus RHE (VRHE ) under AM 1.5 G. The synergetic surface passivation and the co‐catalyst modification contribute to prolonging the charge lifetime, to promoting the charge transfer, and to decreasing the overpotential for water oxidation. Abstract : Zeolitic imidazolate framework‐8 is introduced as the first metal‐organic framework based transparent surface passivation layer for a photo‐electrochemical water‐splitting system with significantly enhanced water oxidation activity and durability.